Gender, sexuality, and the Bible teaching for social justice - Graybill, Rhiannon 1984- (2020)
Courses on the Bible, gender, and sexuality offer many opportunities to promote social justice in the classroom. Instead of emphasizing course content, this article focuses on practical strategies and tactics that incorporate social justice into the everyday teaching of these courses. Drawing on feminist, queer, and affect theory, as well as practical experience, I propose and discuss four questions for assessing classroom practices and materials: Is it welcoming?, Does this joy need to be killed?, Does it work?, and Is it fun? The article also addresses topics such as course design, the selection of readings, assessment, and course pacing from the perspective of teaching for social justice.
Keywords: Spaßverderber